Model Pembinaan Akhlak di Pesantren Mahasiswa Al Jihad Surabaya dan Implikasinya terhadap Pengembangan Pembelajaran PAI di PTU - Much. Imam Rofi’ Rizqi; Syahidin Syahidin; Aam Abdussalam (Jurnal Pendidikan Tambusai, 2022)
Moral decadence is a matter of concern among students or young people today. Behavior that is far from religious teachings, such as drinking, brawls, free sex, abortion, drugs, is something that worries many people, especially parents. Among the factors are technological advances, the environment and lack of parental supervision and lack of instilling religious teachings in their children. At first the learning environment is formed from small groups, namely families, it will give birth to a person's character. In general, if the family environment is good, then noble character will be created and vice versa. In addition to the family environment, there is also another environment that helps shape and foster students' morals formally, namely the school environment. In public schools, including at the public higher education (PTU) level, moral education is taught formally through Islamic Religious Education (PAI) courses. The goal is that students are able to practice religious teachings correctly and consistently. The two environments above do not seem to be sufficient to produce graduates who are able to integrate religious teachings with their respective disciplines, therefore it is necessary to find a learning environment that is able to integrate the understanding of religious teachings according to their respective expertise. The environment is that the student boarding school environment is thought to be able to integrate the values of religious teachings obtained from the family and school environment. This study took the object at the Al-Jihad Student Islamic Boarding School Surabaya. Through a qualitative research approach, it was found that this pesantren has approaches, strategies, methods, techniques in guiding its students to have good character. Al-Jihad Islamic Boarding School uses salafiyah-based learning and integrates it with a modern approach. The educational material examines various books from the salaf and modern scholars and integrates them into a learning model. From this learning model, it is hoped that students and graduates will be able to answer problems according to the challenges of the times. The learning model in Al-Jihad is through habits, such as community service, mutual cooperation, tahajjud, and other practices so that they get used to the good things after completing education at Islamic boarding schools and can feel the benefits.